Dampak Pernikahan Dini terhadap Pelaku dan Tanggung Jawabnya Sebagai Orang Tua kepada Anak - Hidayati Suhaili (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Early marriage is a complex problem that can lead to various psychological, social, and economic impacts. Not only does it affect couples who do marriage, but also to the child born of the outcome of the marriage. The purpose of this study is to know the impact of early childhood marriage to the perpetrator and its responsibilities as a parent in Jorong Koto Tangah Kenagarian Koto Lamo, subdistrict Kapur IX, District fifty cities. Research conducted in Jorong Koto Tangah Kenagarian Koto LamoKecamatan lime IX. This research is a descriptive study. The informant of this research is where teenagers conduct early marriage and the parents of the Nagari informant, religious leaders. Data collection techniques with field studies, interviews, in-depth and observation. Data that can be reconstructed and then analyzed and compiled in the form of tables and questions and answers between researchers clear and qualitative data analysis techniques using techniques expressed by Miles and Hubermen and data collection measures, data reduction, data presentation, withdrawal of conclusions. The results of the study show that early marriage caused a psychological disorder in the form of shame and envy, child social impact, and frequent problems in the family. Married couples at an early age, because the background of education is lacking so that the lack of responsibility as a parent. This is also due to the previous mental and physical unpreparedness.